Childbirth experience questionnaire (CEQ): development and evaluation of a multidimensional instrument - Bergqvist Liselotte; Taft Charles; Dencker Anna; Lilja Håkan; Berg Marie (BMC, 2010)
Abstract Background Negative experiences of first childbirth increase risks for maternal postpartum depression and may negatively affect mothers' attitudes toward future pregnancies and choice of delivery method. Postpartum questionnaires assessing mothers' childbirth experiences are needed to aid in identifying mothers in need of support and counselling and in isolating areas of labour and birth management and care potentially in need of improvement. The aim of this study was to develop and evaluate a questionnaire for assessing different aspects of first-time mothers' childbirth experiences. Methods Childbirth domains were derived from literature searches, discussions with experienced midwives and interviews with first-time mothers. A draft version of the Childbirth Experience Questionnaire (CEQ) was pilot tested for face validity among 25 primiparous women. The revised questionnaire was mailed one month postpartum to 1177 primiparous women with a normal pregnancy and spontaneous onset of active labor and 920 returned evaluable questionnaires. Exploratory factor analysis using principal components analysis and promax rotation was performed to identify dimensions of the childbirth experience. Multitrait scaling analysis was performed to test scaling assumptions and reliability of scales. Discriminant validity was assessed by comparing scores from subgroups known to differ in childbirth experiences. Results Factor analysis of the 22 item questionnaire yielded four factors accounting for 54% of the variance. The dimensions were labelled Own capacity, Professional support, Perceived safety, and Participation. Multitrait scaling analysis confirmed the fit of the four-dimensional model and scaling success was achieved in all four sub-scales. The questionnaire showed good sensitivity with dimensions discriminating well between groups hypothesized to differ in experience of childbirth. Conclusion The CEQ measures important dimensions of the first childbirth experience and may be used to measure different aspects of maternal satisfaction with labour and birth.